Coming up roses - Anderson, Catherine (Adeline Catherine) (New York : Signet, 2012)
"1890, Oregon: recently widowed, Kate Blakely is struggling to make ends meet on her small farm as she tries to heal from the scars of her late husband's cruelty. When her handsome, brawny neighbor Zachariah McGovern almost dies while saving her four-year-old daughter from a near-fatal accident, Kate, despite being deeply wary of the man, brings him into her home to nurse him back to health. Gradually Kate realizes that underneath Zach's rough exterior is a gentle, loving soul who is fiercely protective of Kate and her daughter. But at much as Zach longs for Kate's love, she knows she can't open her heart without revealing her darkest secret"--P. [4] of cover.
Originally published: 1993.
Includes an excerpt from the author's: Lucky penny (p. [405]-419).
Keywords: Widows -- Fiction; Single mothers -- Fiction; Farmers -- Fiction; Farm life -- Oregon -- 19th century -- Fiction; Man-woman relationships -- Fiction; Oregon -- Fiction; Love stories; Historical fiction